Isolasi, Seleksi, dan Identifikasi Bakteri Endofit sebagai Agens Penginduksi Ketahanan Padi terhadap Hawar Daun Bakteri - Ida Parida; Tri Asmira Damayanti; Giyanto Giyanto (The Indonesian Phytopathological Society (Perhimpunan Fitopatologi Indonesia), 2016)
Bacterial leaf blight caused by Xanthomonas oryzae pv. oryzae is one of the major problems in rice production in Indonesia. One of the control measures for the disease is by the utilization of endophytic bacteria. This study was aimed to determine the ability of endophytic bacteria isolated from the roots, stems and leaves of rice in inducing plant resistance to bacterial leaf blight on rice. Screening of endophytic bacteria showed that 370 isolates have good viability and have different colony morphology. Among them, 7 isolates were able to induce resistance and 1 isolate was able to promote the growth of rice in the nursery. However, only 8 isolates did not cause hypersensitive reaction on tobacco plants. The selected isolates of endophytic bacteria were further examined for their ability to induce resistance of rice in greenhouse experiments. Observation involved several variables, i.e. PR1 and PBZ1 gene expression, peroxidase enzyme activity, incubation period, and disease progression. Seven isolates of endophytic bacteria were able to induce PR1 and PBZ1 gene expression, 4 isolates were able to increase peroxide enzyme activity, 4 isolates could prolong the incubation period, and 2 isolates can inhibit the development of disease. However, only EB4 451 isolate was consistently able to induce PR1 and PBZ1 gene expression, increased peroxide enzyme activity, prolonged incubation period, and suppressed the progression of the disease. The EB4 451 isolate was identified based on nucleotide sequence as Bacillus subtilis.